ENVIRONMENTAL IMPACT ANALYSIS OF EXTERNAL AND INTERNAL BUSINESSES AGAINST THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES - Firman Bachtiar; Agus Dwi Atmoko; Danis Imam Bachtiar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to obtain empirical evidence and find an explanation of the phenomenon of external and internal business environmental impacts on the performance of Small and Medium Enterprises (UKM) Tenant Business Incubators of the Sawunggalih Aji Polytechnic, Purworejo Regency. This type of research is a descriptive study of 60 respondents. Data is collected through notes or documents and in-depth interview techniques sourced from information from tenants in the Business Incubator. Data were analyzed using quantitative analysis and qualitative analysis. The results of research on the strategy of the Small and Medium Enterprises level in the Tenant Business Incubator in Strategic Planning in anticipating changes in the External and Internal Business Environment in the development of SMEs. It can also be explained by the political, security, and legal environment and the economic, technological, social, and cultural environment. Internal business environment variables can be explained by Product Development, Sales, and After Sales Services, and the target Performance Variables are Return On Assets, Return On Investment, and Return On Equity.